2008
DOI: 10.1016/j.cognition.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal interactions in the experience of musical performances: Physiological correlates

Abstract: This experiment was conducted to investigate cross-modal interactions in the emotional experience of music listeners. Previous research showed that visual information present in a musical performance is rich in expressive content, and moderates the subjective emotional experience of a participant listening and/or observing musical stimuli [Vines, B. W., Krumhansl, C. L., Wanderley, M. M., & Levitin, D. J. (2006). Cross-modal interactions in the perception of musical performance. Cognition, 101, 80–113.]. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 48 publications
3
77
3
2
Order By: Relevance
“…Although previous studies have shown that visual information can influence the emotions induced by a musical performance (e.g., Chapados & Levitin, 2008;Krahé et al, 2013;Timmers, Marolt, Camurri, & Volpe, 2006, Vines et al, 2011, they haven't been able to reliably estimate the effects size of visual performance cues relative to that of auditory performance cues. The present study revealed that -in terms of the emotional impact of musical performances -the contribution of visual kinematic performance cues appears to be comparable to that of auditory performance cues.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Although previous studies have shown that visual information can influence the emotions induced by a musical performance (e.g., Chapados & Levitin, 2008;Krahé et al, 2013;Timmers, Marolt, Camurri, & Volpe, 2006, Vines et al, 2011, they haven't been able to reliably estimate the effects size of visual performance cues relative to that of auditory performance cues. The present study revealed that -in terms of the emotional impact of musical performances -the contribution of visual kinematic performance cues appears to be comparable to that of auditory performance cues.…”
Section: Discussionmentioning
confidence: 88%
“…Hargreaves & North, 2010). Although there is some evidence to indicate that visual information might enhance emotional reactivity to musical performances (Chapados & Levitin, 2008), it is not yet known how the effect of visual performance cues relates to that of auditory performance cues with regard to the subjective emotional reaction of the observer. Furthermore, the explicit instructions used by Vuoskoski et al to take both auditory and visual aspects of the performance into account in the evaluations of overall expressivity might have affected which aspects of the material the participants attended to (for details, see Vuoskoski et al, 2014; Experiment 1).…”
Section: Usic Is An Inherently Multisensorymentioning
confidence: 99%
See 2 more Smart Citations
“…31 EDA generally followed similar contours in all three conditions. Correlations between EDA and subjective measures of tension from the original study were strongest for the AV condition.…”
Section: Figurementioning
confidence: 67%